Sr–Nd isotopes of Early and Late Carboniferous volcanic rocks in Yining Massif (Xinjiang, NW China): Implications for petrogenesis and tectonic evolution of Western Tianshan. (6th March 2018) - Tong, Lili; Li, Yongjun; Li, Ganyu; Li, Zhucang; Yang, Gaoxue; Wang, Zuopeng; Wang, Zhenyu; Shen, Rui; Li, Zhao
Abstract : The Yining Massif, sandwiched between the Junggar and Tarim plates, has received much attention because of its special position and complex tectonic evolution, as well as a significant breakthrough in geological prospecting. Moreover, a lot of studies have focused on two suites of volcanic rocks of the Early Carboniferous Dahalajunshan and Late Carboniferous Yishijilike formations in the Yining Massif. Recently, an increasing number of results have shown that two suites of volcanic rocks have obvious differences in lithochemistry and geochemistry and might have formed in an arc and intracontinental rift settings, respectively. Furthermore, the latest results of Sr–Nd isotopes indicate that the initial ( 87 Sr/ 86 Sr)i ratio is less than 0.7119 for all samples in the two formations. But the ( 87 Sr/ 86 Sr)i of andesites in the Dahalajunshan Formation is obviously higher than that of the Yishijilike Formation. However, those of dacites and rhyolites are just the opposite. The ( 143 Nd/ 144 Nd)i of all kinds of rocks from the Dahalajunshan Formation is less than 0.5126, and that of basalts in Yishijilike Formation is also less than 0.5126. However, the results of the andesites and rhyolites are higher than 0.5126. In short, the parameters of ( 87 Sr/ 86 Sr)i, ( 143 Nd/ 144 Nd)i, εNd( t ), T DM (Ga), and εSr(t) are different obviously between the two suites, showing progressive change from basic to acid rocks in the two formations (gradual increase and decrease), but the changed direction is just the opposite. Consequently, it illustrates that there is a significant distinction in composition and petrogenesis between the Dahalajunshan and Yishijilike formations. The Dahalajunshan Formation volcanic rocks might be derived from an enriched mantle, whereas the volcanic rocks in the Yishijilike Formation are related to the evolution of continental crust. In other words, the differentiation of Sr–Nd isotopes provides a reference information for studying the petrogenesis and tectonic setting of the two suites of volcanic rocks.